T H E R O L E O F ENGLISH WORD AND PSEUDOWORD SPELLING PERFORM ANCES TURKISH STUDENTS ACROSS GRADES 6, 7, AND 8. - Melike Ünal Gezer; L. Quentin Dixon (Informascope, 2017)
The purpose of the present study was to explore the role of English as a foreign language (EFL) phonology, morphology, and orthography knowledge of native Turkish EFL students in predicting the EFL spelling performance across grade levels. Tests tapping into various metalinguistic knowledge in English including EFL real and pseudoword spelling and English phonological, morphological, and orthographic processing skills were administered to 6th, 7th and 8th graders. Statistical analyses of the data revealed converging results that these skills are highly correlated with each other and they each have an impact on the EFL spelling outcomes of Turkish middle graders. Further regression analyses suggested that Turkish middle graders' EFL phonology knowledge predicted their real and pseudoword spelling outcomes the most compared to their EFL morphology and orthography knowledge. The results of the present study were discussed in terms of the phonetic nature of Turkish language as well as the EFL pedagogy. The key findings aimed to inform foreign language teachers about the roles of phonological, morphological, and orthographic processing skills in English word spelling.